IMPROVING MINI VOLLEYBALL BASIC MOVEMENT MANIPULATING SERVICE LEARNING OUTCOMES USING THE TARL METHOD IN CLASS IV STUDENTS OF SD PUCANGSAWIT SURAKARTA CITYâ€ - abdul latif, annas (JUARA : Jurnal Olahraga, 2025)
This study aims to improve the learning outcomes of the basic manipulative movement of the underhand serve of a mini volleyball using the TaRL method for fourth grade students at SD Negeri Pucangsawit Surakarta. Using the TaRL method, namely learning that is divided into different levels starting from easy, medium, and difficult level. As well as students choosing their own learning according to their abilities aims to provide self-motivation for students because students can compete with friends who have the same abilities, and achieve the final goal at difficult level learning, and for students will be directed to a mini volleyball game which is modified after passing difficult level. This research is a class action research (CAR). This research was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The research subjects were fourth grade students at SD N Pucangsawit Surakarta, totaling 29 students consisting of 16 boys and 13 girls. Sources of data come from teachers, students, and researchers. Data collection techniques using data triangulation techniques. Data analysis uses a comparative descriptive technique by using techniques to see trends that occur in learning activities. The results of the data analysis can be summarized as follows: learning outcomes for the basic manipulative movement of serving under mini volleyball, pre-cycle seen from the psychomotor aspect, 21% complete, cognitive 15% complete, affective 100%, cycle I psychomotor 45% complete, cognitive 41% complete, affective 100%, and cycle II psychomotor 83%, cognitive 81%, affective 100% complete. Based on these three aspects there was an increase of 45% complete pre-cycle, 62% complete first cycle, and 88% complete second cycle. Based on the results of the data analysis above, it can be concluded that the use of the TaRL method can improve learning outcomes for the basic manipulative movement of the underhand mini volleyball in class IV students at SD Negeri Pucangsawit Surakarta